Resistance exercise intervention on muscular strength and power, and functional capacity in acute hospitalized older adults: a systematic review and meta-analysis of 2498 patients in 7 randomized clinical trials - Carneiro, Marcelo A. S.; Franco, Cristiane M. C.; Silva, Alan L.; Castro-e-Souza, Pâmela; Kunevaliki, Gabriel; Izquierdo, Mikel; Cyrino, Edilson S.; Padilha, Camila S. [UNESP] (Springer Nature, 2021)
Abstract: To date, no meta-analytical study evaluating the benefits of resistance exercise intervention on muscular strength and power and functional capacity in acute hospitalized older adults was conducted. Then, to synthesize the emerging evidence on the effects of resistance exercise intervention on muscular strength and power and functional capacity in acute hospitalized older adults, two independent authors performed a systematic search (PubMed, Scopus, Web of Science, and SciELO) until January 2021. Randomized clinical trials were included regarding the effects of resistance exercise and hospital usual care. The Cochrane Collaboration assessment tool was used to analyze the risk of bias. The comparisons included muscular strength (isometric handgrip strength and one-repetition maximum test of leg press), muscular power (output during leg press exercise), and functional capacity (timed-up-and-go, and short physical performance battery). Resistance exercise intervention increased muscular strength (isometric handgrip strength: mean difference = 2.50 kg, 95% confidence interval (CI) = 1.33, 3.67; and one-repetition maximum test of leg press: mean difference = 19.28 kg, 95% confidence interval = 14.70, 23.86) and muscular power (mean difference = 29.52 W, 95% confidence interval = 28.84, 30.21), and functional capacity (timed-up-and-go: mean difference = 3.40 s, 95% confidence interval = 0.47, 6.36; and short physical performance battery: mean difference = 1.29 points, 95% confidence interval = 0.10, 2.48) at discharge compared with hospital usual care. This meta-analysis endorses the increase of muscular strength and power gains and improving the functional capacity in favor of resistance exercise intervention in acute hospitalized older adults. Trial Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020203658
Keywords: Aging; Inflammation; Older adults; Physical performance; Strength training